Juridical Analysis of Legal Protection for Malpractice Victims by Hospitals in Patients with Brain Stem Death Post Tonsillectomy as Regulated by Law Number 8 of 1999 Concerning Consumer Protection and Law Number 17 of 2023 Concerning Health - Prayuti, Yuyut; Sienty Effendy, Meyland Citra Oktri; Wardani, Dita Nur; Harinawantara, Hangga; Asfihani, Nadya Zhafira (Universitas Ekasakti, 2023)
The aim of this study is to examine and comprehend the legal foundation and implementation of legal protection for victims of malpractice by hospitals in Indonesia. This research seeks to assess the degree to which victims of malpractice receive legal protection and hold hospitals and involved medical personnel accountable. The research methodology employed is a literature study, encompassing secondary data collection through books, law journals, research findings, and pertinent legislative documents. Various legal sources are scrutinized in this research, including Law Number 8 of 1999 on Consumer Protection and Law Number 17 of 2023 on Health. The findings reveal that there are legal frameworks providing protection for victims of malpractice, such as Law No. 44 of 2009 on Hospitals and Health Law No. 17 of 2023. Nonetheless, challenges persist in the implementation of legal protection for malpractice victims, particularly concerning the legal procedures that victims must navigate to secure compensation and accountability from hospitals or medical personnel.